2018
DOI: 10.1021/acsomega.8b01890
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Efficiency of a Least Active Ag–TiO2 by Amine Adsorption

Abstract: An Ag–TiO 2 photocatalyst with 3.5 atom % silver content, synthesized by a single step sol–gel method, possessed silver nanoparticles (AgNPs; 1–5 nm) on the TiO 2 surface, but owing to the nonplasmonic nature of AgNPs and the wide band gap of TiO 2 , this material exhibited poor activity in a photocatalytic degradation reaction. However, this least active Ag–TiO 2 catalyst showed a sudden increase in activity during a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…The SPR is sensitive to changes in the local dielectric environment. Among noble metal nanoparticles, AgNPs has the highest efficiency of plasmon excitation in the visible spectrum due to the different dielectric properties originated from the small overlap between the SPR and the interband transition in silver from 4d electrons to the hybridized 5sp band that starts at 320 nm [9,26]. There have been many studies that have characterized the good correlation between change in SPR spectral absorbance on both physical change and behavior of AgNPs in suspension [8,9,18], thus UV-vis spectroscopy can be a fast and easy analytical tool to monitor AgNPs properties in the suspension.…”
Section: Resultsmentioning
confidence: 99%
“…The SPR is sensitive to changes in the local dielectric environment. Among noble metal nanoparticles, AgNPs has the highest efficiency of plasmon excitation in the visible spectrum due to the different dielectric properties originated from the small overlap between the SPR and the interband transition in silver from 4d electrons to the hybridized 5sp band that starts at 320 nm [9,26]. There have been many studies that have characterized the good correlation between change in SPR spectral absorbance on both physical change and behavior of AgNPs in suspension [8,9,18], thus UV-vis spectroscopy can be a fast and easy analytical tool to monitor AgNPs properties in the suspension.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the improved charge-carrier separation and/or transport efficiency, it has been shown that enhanced photocatalytic activity can also arise from enhanced adsorption properties. 36,37 To investigate this enhancement mechanism, the adsorption properties of AO7 on TiO 2 nanocrystals prepared under different doping conditions were studied using UV-vis spectroscopy. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from in electron-hole separation efficiency, it has been shown that the enhancement in photocatalytic activity of metal-TiO 2 systems might also arise from an improvement in adsorption properties. [45,46] To study this the adsorption of MO on TiO 2 and Au (15) -TiO 2 SENSs were studied using UV-vis spectroscopy. As shown in Figure S9, Supporting Information, the adsorption kinetics and capacity of the TiO 2 and Au (15) -TiO 2 SENSs were found to be identical, which suggests that the enhancement in photocatalytic activity of the Au (15) -TiO 2 SENSs arose mainly from improved electronhole separation efficiency due to the Au NPs acting as electron sinks.…”
Section: Resultsmentioning
confidence: 99%